2010
DOI: 10.1080/09640568.2010.490060
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of a hydroelectric project on the flora in the Western Himalayan region based on vegetation analysis and socio-economic studies

Abstract: This study provides an overview of the impacts of a proposed hydroelectric power project in the Western Himalayan region in India, using a primary database on floristic diversity and vegetation analysis. The remote sensing data revealed that in the submergence zone only mixed deciduous forest that occupies 807.5�ha area and has a wood biomass volume of 4,027,503�m3 is likely to be lost due to impoundment. A total of 165 plant species found in the submergence zone also occur in the influence and free draining c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the case of HE, river flows are critical to ecosystems [138], and any alterations of the river flow can impact aquatic ecosystems [139]. Like other forms of RE, studies have identified different negative biodiversity impacts of large HE projects [140][141][142][143]. Therefore, the scale of the dams and their impacts on local ecosystems being prominent elements for consideration of the justice dimensions of HE development [144,145,146].…”
Section: Temporal Dimension Of Justice In Renewable Electricitymentioning
confidence: 99%
“…In the case of HE, river flows are critical to ecosystems [138], and any alterations of the river flow can impact aquatic ecosystems [139]. Like other forms of RE, studies have identified different negative biodiversity impacts of large HE projects [140][141][142][143]. Therefore, the scale of the dams and their impacts on local ecosystems being prominent elements for consideration of the justice dimensions of HE development [144,145,146].…”
Section: Temporal Dimension Of Justice In Renewable Electricitymentioning
confidence: 99%